Kebijakan Penataan Ruang Terbuka Hijau di Kota Malang - Praptining Sukowati (Magister Administrasi Publik, 2012)
The firs purpose of the research is to analyze the sustainable development policies and public participation to the Green Open Space's shifting function in Malang. The second is to analysis the factors that binder the policy implementation process. This paper shows that public participation in the sustainable development policies is less than optimal. Some factors that impede the policy implementation are 1) inadequate provision of GOS both in quantity and quality; 2) many weakness in the institution who manage the GOS; 3) the weak role of the stakeholders; 4) the use of open land for GOS function is not optimal yet. Some of the recommendation of this research include the need to revise UU No.24/1992; to develop guidelines for the implementation of GOS's management; to improve the campaign about the importance of GOS through